2015
DOI: 10.1080/02602938.2015.1103365
|View full text |Cite
|
Sign up to set email alerts
|

Feedback on feedback practice: perceptions of students and academics

Abstract: While feedback is widely considered central to student learning, students across the higher education sector commonly report dissatisfaction with the feedback they receive. In contrast, academics often feel they provide quality and informative feedback. This article explores and compares the perceptions of students and academics with regard to feedback practice. The paper presents the results of questionnaire surveys conducted with academics and students at the School of the Built Environment, Liverpool John M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
167
2
5

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 193 publications
(205 citation statements)
references
References 56 publications
9
167
2
5
Order By: Relevance
“…I noted in my journal that when students received their rubrics, they appeared to glance at the final grade, and then placed the paper in their backpacks. This is consistent with the findings of Mulliner & Tucker () about students’ lack of focus on feedback, regardless of the volume of writing or printing. Coaching and dialog are needed to encourage students to take ownership of the assessment feedback (Adams et al .…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…I noted in my journal that when students received their rubrics, they appeared to glance at the final grade, and then placed the paper in their backpacks. This is consistent with the findings of Mulliner & Tucker () about students’ lack of focus on feedback, regardless of the volume of writing or printing. Coaching and dialog are needed to encourage students to take ownership of the assessment feedback (Adams et al .…”
Section: Resultssupporting
confidence: 92%
“…However, as I wrote more, millennial students seemed to read less and appeared to reject more completely the feedback. This observation is validated in the study by Mulliner & Tucker (2015) who surveyed millennial students about feedback. They found that individual typed and hand-written feedback were perceived as very effective by less than one-half of the responding students.…”
Section: Time Constraintsmentioning
confidence: 59%
“…There were no significant differences between the two cohorts when students were asked to rank feedback type by order of importance. Mulliner and Tucker (2015) found that students in their study preferred verbal to written feedback. Whereas, the present study showed no preference between verbal and written comments in students' first choice of feedback, and when combining first and second choices, written feedback was rated higher than verbal feedback.…”
Section: Discussionmentioning
confidence: 94%
“…Large discrepancies have been documented between the expectations of students in their first year of higher education and those of their tutors (Yorke and Longden 2008). Mulliner and Tucker (2015) asked students about their perceptions of feedback and found that they were expecting personal verbal feedback from teachers. This supports the present study where 80 % of students were expecting personal verbal feedback from their lecturers.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation